2017
DOI: 10.1149/2.0671706jes
|View full text |Cite
|
Sign up to set email alerts
|

SVET Study of Galvanic Corrosion of Al/Mg2Si Couple in Aqueous Solutions at Different pH

Abstract: The galvanic corrosion behavior between pure Al and synthesized bulk Mg 2 Si in 0.01 M NaCl solution at different pH values has been investigated by the scanning vibrating electrode technique (SVET). At pH 2, bulk Mg 2 Si actively dissolves and it acts as an anode. With the increase of exposure time, the anodic activity of Mg 2 Si decreases drastically and eventually anodic activity appears on Al surface. In alkaline solution, Mg 2 Si phase always acts as the cathode. The preferential dissolution of Mg and enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…In dry atmosphere, the surface of metals is usually covered by a dense and protective (passive) metal-oxide layer which impedes corrosion reactions [67][68][69]. It has been reported that the surface of Mg 2 Si can form a passive oxide layer [70][71][72], which grows with time and results in an enhanced electrochemical nobility in both ambient air and corrosive environments [71]. The investigated sample was exposed to laboratory air for 2 months, allowing the formation of oxide/hydroxide on the surface (aging).…”
Section: Discussionmentioning
confidence: 99%
“…In dry atmosphere, the surface of metals is usually covered by a dense and protective (passive) metal-oxide layer which impedes corrosion reactions [67][68][69]. It has been reported that the surface of Mg 2 Si can form a passive oxide layer [70][71][72], which grows with time and results in an enhanced electrochemical nobility in both ambient air and corrosive environments [71]. The investigated sample was exposed to laboratory air for 2 months, allowing the formation of oxide/hydroxide on the surface (aging).…”
Section: Discussionmentioning
confidence: 99%
“…These results are concordant with reports in the literature. 6,7,13,33 SVET maps reveal that severity galvanic coupling effect is well pronounced in very acidic or alkaline environment. MgZn 2 is anodic relative to Al at pH 2 but cathodic relative to Al at pH 12, while self-dissolution prevails under near neutral conditions with Al being almost in a passive state (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The SVET results provided a good spatial resolution which clearly demonstrates that it is possible to get complementary data supporting the physical interpretations of the galvanic corrosion processes based on the application of traditional electrochemical techniques. 13,15,19,20 …”
Section: Comparison Of Positive Ionic Current Densities On Coupled Anmentioning
confidence: 99%
See 2 more Smart Citations